Jamaica : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that following the near crisis in the first half of 2003, the authorities in Jamaica have succeeded over the past year in stabilizing the economy and restoring market confidence. The foreign exchange market stabilized in mid-2003, inflation has decelerated, domestic interest rates have declined, and growth improved, while Jamaica has returned to the international capital market. Real GDP growth reached 2 percent in FY 2003/04. The improvement was led by strong performance in the key tourism and mining sectors.